Liquid Sugar from Egyptian Treacle: 1. A Study of some Characteristics of the Colouring Matters Isolated from Egyptian Treacle - MOHAMED, MOSTAFA A. (The Libyan Journal of Agriculture, 2023)
The present investigation was performed in an attempt to study the possibility of obtaining liquid sugar from Egyptian treacle, a matter considered to be of great practical importance in food industries. The samples of treacle were chemically analysed to determine their average composition. The colouring matters of treacle were isolated and further studied.It was found that the colouring matters had an indicator property. The presence of coloured complexes of polyphenols with metals was predicated. The detection of six amino acids in composition of the colouring matters under study emphasized the presence of melanoidines group among their colour components. The elemental analysis of the isolated polymers was as follows: C, 41.69; H, 6.59; N, 5.04; 0, 42.36; ash, 4.32. An empirical formula for the repeating unit in these polymers, C9 10 HI8 I9 O7 8 N, was deduced from the elemental analysis.The infrared spectrum of these polymers showed at least ten significant bands indicative of the functional groups: =N—H. —C = N, —NH3, —C = C—, R. CH =CH2, O C O and —CH3.N Model coloured solutions were prepared under conditions similar to those which prevail during the manufacturing process of treacle. The intensity of the developed colour was measured during the heating process of these solutions. Some physicochemical properties of the groups of colourants obtained were also studied. The effect of Fe ’ ’ and Cu’ ’ ions on the acceleration of colour reactions was studied. It was found that these ions, which originated from the equipment during the manufacturing processes, changed not only the intensity of colour in the visible region of spectra, but also the character of the absorption spectra for the solutions in the U.V. region. The results obtained gave an evidence that the colouring matters of treacle contained one or more of the groups of model colourants.